Mineralogical study of a soil belonging to the fundo fruit nursery Motupe Lambayeque, using analytical and complementary techniques - Trujillo, Alejandro (2018)
The products derived from the weathering process of soils can be removed from this system by the process of water drainage or they can react in this system by forming a variety of crystall or amorphous products. The reaction products that are most commonly observed are the clay minerals, the oxides and hydroxides iron and aluminum. The characterization of these materials is of vital importance because they reflect at its best the long term effects of the chemical environment and draining mechanisms of soils. Moreover, they have a marked influence on many soil properties. This paper reports the results of the elemental and mineralogical characterization of a soil sample from the Motupe orchard and nursery farm that belongs to the Pedro Ruiz Gallo National University, Lambayeque, using X-ray Fluorescence (XRF), X-ray Diffraction (XRD) and Transmission Mössbauer Spectroscopy (EMT) techniques were used. Other routine soil analysis were also applied such as texture, pH, electrical conductivity and percent content of carbonates and bicarbonates. The Mo06 sample bulk was tested. By XRD was identified. Quartz, Illite, Orthoclase and Albite. In the bulk sample by TMS was identified a sextet attributed to Hematite, a central doublet that could be assigned to an iron oxide in the super paramagnetic state and two doublets assigned to the Illite. The chemical composition, for elements with atomic number higher than 13, was determines by XRF. Iron and silicon were determine to be the major components, and Sulfur, Chlorine, Potassium, Calcium, Titanium, Vanadium, Chrome, Manganese, Nickl, Copper, Zinc, Rubidium, Strontium and Zirconium as minor components. Number larger than 13, and Zinc, Rubidium, Strontium and Zirconium as minor components.